2022
DOI: 10.21511/ppm.20(3).2022.30
|View full text |Cite
|
Sign up to set email alerts
|

How does strategic flexibility make a difference for companies? An example of the Hungarian food industry

Abstract: Nowadays, strategic flexibility and its effect on organizational performance are crucial to discuss. Moreover, organizations, especially industrial companies, should estimate how flexibility as a mechanism can improve organizational performance. The Hungarian food industry is highly significant in the industrial sector of the Hungarian economy. Therefore, the aim of this paper is to evaluate how the performance of the Hungarian food industry is affected by strategic flexibility, using supply and demand uncerta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 61 publications
(39 reference statements)
1
11
0
1
Order By: Relevance
“…Network capability and business model also enhance the positive effect of SF on firm performance [ 51 ]. In the Hungarian food industry, the performance affected by SF was evaluated, and it was found that in total, 66.5% of changes in companies’ performance are related to SF [ 52 ]. In the textile industry, fashion industry, hotel industry and Chinese sea food industry, SF allow firms to overcome competitive disadvantages and compete effectively against larger firms in the market and has a significant effect on business performance as well [ 53 , 54 , 55 , 56 ].…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Network capability and business model also enhance the positive effect of SF on firm performance [ 51 ]. In the Hungarian food industry, the performance affected by SF was evaluated, and it was found that in total, 66.5% of changes in companies’ performance are related to SF [ 52 ]. In the textile industry, fashion industry, hotel industry and Chinese sea food industry, SF allow firms to overcome competitive disadvantages and compete effectively against larger firms in the market and has a significant effect on business performance as well [ 53 , 54 , 55 , 56 ].…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…A termelés hatékonyságának javítása a rendelkezésre álló modern technológia, automatizálás, digitalizálás és a szükséges szakértelem komplex alkalmazásával biztosítható (Takácsné és Takács, 2016;Rajczi et al, 2017, Szőllősi et al, 2021. A hatékony gazdálkodás mellett a vállalati teljesítmény fokozása érdekében napjainkban a hagyományos vezetési technikákon túl a stratégiai (Yousuf at al., 2022) és a működési (Yousuf et al, 2019) rugalmasság alkalmazása is kiemelt figyelmet kap. Az Európai Unió szántóterülete mintegy 99 millió hektár, melynek közel 17 százalékát Magyarország, Szlovákia és Lengyelország adta 2018-2020 között (FAOSTAT, 2022).…”
Section: Bevezetésunclassified
“…Enhancing production efficiency can be ensured through the application of available modern technology, automation, digitalization, and the necessary expertise [16,[24][25][26]. In addition to efficient management, enhancing corporate performance nowadays also emphasizes the use of strategic [27] and operational [28] flexibility, going beyond traditional management techniques.…”
Section: Literature Reviewmentioning
confidence: 99%